From Technology to Tradition Students learning in Taiwan opens their eyes to a wider world - Nor Azlina, Ahmad (UMPSA, 2024)
TAIPEI, TAIWAN, 26 November 2024 – A total of 17 students and staff from Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) recently participated in the International Mobility Programme in Taipei, Taiwan.